1987
DOI: 10.2527/jas1987.6451395x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of Glucose and Fatty Acid Metabolism of Liver, Kidney, Skeletal Muscle, Adipose Tissue and Mammary Gland of Lactating and Non-Lactating Sheep

Abstract: The effect of peak lactation on the activities of a number of enzymes of glucose and lipid metabolism of perirenal and subcutaneous adipose tissue, skeletal muscle, liver, kidney cortex and mammary parenchyma of sheep are described. Enzymes studied included hexokinase (glucose utilization), pyruvate carboxylase (gluconeogenesis), pyruvate dehydrogenase (glucose oxidation and production of acetyl CoA for fatty acid synthesis), acetyl CoA carboxylase (fatty acid synthesis) and glycerol-3-phosphate acyltransferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
1
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 58 publications
5
22
1
1
Order By: Relevance
“…To our knowledge, very little data are available concerning the lipogenic activities of muscles depending on their metabolic types. However, one study reported a 2-fold greater G3PDH activity in skeletal muscles than in s.c. adipose tissue in sheep (Vernon et al, 1987), which was also observed in our study. From these results, we conclude that in muscles from steers, G3PDH is not only involved in TAG synthesis but probably also in the glycerol phosphate shuttle (Estabrook and Sacktor, 1958).…”
Section: Differences Between Anatomical Sites For Lipid Anabolismsupporting
confidence: 78%
See 2 more Smart Citations
“…To our knowledge, very little data are available concerning the lipogenic activities of muscles depending on their metabolic types. However, one study reported a 2-fold greater G3PDH activity in skeletal muscles than in s.c. adipose tissue in sheep (Vernon et al, 1987), which was also observed in our study. From these results, we conclude that in muscles from steers, G3PDH is not only involved in TAG synthesis but probably also in the glycerol phosphate shuttle (Estabrook and Sacktor, 1958).…”
Section: Differences Between Anatomical Sites For Lipid Anabolismsupporting
confidence: 78%
“…To our knowledge, breedrelated leptin gene expression in muscles has never been reported before. Because leptin mRNA level in bovine is high in adipose tissue but barely detectable in muscle (Chelikani et al, 2003), and most of the lipogenic enzymes are more strongly expressed in adipose tissues than in muscles of ruminants (Howarth et al, 1968;Vernon et al, 1987;Belk et al, 1997), the greater G6PDH and MD activities and leptin mRNA level in LT from Angus vs. Limousin steers may result from a greater number of muscular adipocytes, from greater lipogenic activities of these cells, or both. To address this question, we assayed the same variables in the i.m.…”
Section: Muscular Adiposity and Lipid Anabolism Pathways In Muscles Amentioning
confidence: 99%
See 1 more Smart Citation
“…Les variations du gras sous-cutané peuvent être estimées in vivo à partir de la note d'état corporel (Russel et al, 1969), ou par les modifications de la taille des adipocytes sous-cutanés (Thornton et aL, 1983 (Vernon et al, 1981(Vernon et al, , 1987Vernon & Taylor, 1986 …”
unclassified
“…These (Hood, 1982;Rule et al, 1987;Vernon et al, 1987;Gagliostro and Chilliard, 1991 In ruminants, the increase of acetate concentration or availability activates the G6PDH enzyme (Martin et al, 1973;Pothoven and Beitz, 1973;Yang and Baldwin, 1973;Whitehurst et al, 1978). This fact could contribute to explain the increase in G6PDH activity observed in this study from 24 kg LW.…”
Section: Discussionmentioning
confidence: 60%